The grand escape : the greatest prison breakout of the 20th century - Bascomb, Neal (Scholastic Focus, 2020)
Tells the true story of Allied soldiers in WWI who pulled off a daring escape from Germany's most notorious prison camp, Holzminden. Includes historic photographs and diagrams of the escape. Also includes maps, sources for further information, and an index.